Susceptibility ofVibrio Aestuarianus01/032 to the Antibacterial Activity ofMytilusHemolymph: Identification of A Serum Opsonin Involved in Mannose-Sensitive Interactions - Elisabetta, Pezzati; Laura, Canesi; Gianluca, Damonte; Annalisa, Salis; Chiara, Grande; Luigi, Vezzulli; Carla, Pruzzo; MARSANO, Francesco (Environmental Microbiology, 2015)
The interactions of Vibrio aestuarianus 01/032 with hemolymph of the bivalves Mytilus galloprovincialis and Crassostrea gigas were investigated to understand if hemolymph components (hemocytes and soluble factors) could be involved in the higher resistance to microbial infection shown by mussels in comparison to oysters. Although 01/032 bacteria adhered to hemocytes of both bivalves, they were sensitive to the bactericidal activity of whole hemolymph from mussel but not from oyster; in addition, adhesion to mussel (but not oyster) hemocytes was affected by D-mannose. Mussel serum opsonins directed towards D-mannose - binding bacterial ligands were purified by affinity chromatography and were shown to mediate 01/032 interactions with M. galloprovincialis hemocytes. Nano-HPLC-ESI-MS/MS analysis showed that the purified opsonin matched to the protein precursor of the extrapallial protein (EP) [Mytilus edulis]. In the presence of M. galloprovincialis EP protein (MgEP), C. gigas hemocytes killed V. aestuarianus 01/032 almost as efficiently as mussel phagocytes. These findings suggest that the different sensitivity of 01/032 strain to the antibacterial activity of oyster and mussel hemolymph might partly depend on the fact that C. gigas serum lacks MgEP-like opsonins. These results represent the basis for understanding the different sensitivity to microbial infections shown by the two bivalve species.